Comparative study of five country-specific labour-intensive infrastructure development programmes : implications for South Africa - Quainoo, Harry Akyen (University of the Witwatersrand, Johannesburg, 2010)
Unemployment and abject poverty in South Africa are widespread, persistent and disproportionately high. These problems are aggravated by inadequate capacity at all tiers of government and huge infrastructure backlogs in rural South Africa. Employment-intensive means of infrastructure delivery have been successfully implemented in several sub-Saharan African countries and elsewhere to generate employment and reduce poverty. It should be possible to replicate similar large-scale national programmes in South Africa. But South Africa has failed. Both prior to and since 1994, several supposedly employment-intensive programmes have been implemented in South Africa with poor results. In an endeavour to contribute to future South African policy and good practices regarding employment, this thesis describes and analyses in detail five major Sub-Saharan programmes and reaches conclusions regarding their achievements and shortcomings. Lessons derived bridge the knowledge gap between the large-scale programmes embarked upon in the sub-Saharan countries in the mid-1980s and the year 2007; these lessons should be applied to future endeavours in South Africa to generate significant employment per unit of expenditure and contribute to poverty alleviation. A major conclusion reached was that the success of employment-intensive infrastructure development programmes depends to a large extent on fundamental factors such as appropriate and implementable policy, government commitment, adequate and sustainable funding, adequate capacity and good preparation. Specifically, the thesis demonstrated that prior to implementation a sufficient timeframe is required for programme preparation in order to make significant contribution towards poverty reduction. Equally, national programme expansion requires a strategic balance between centralisation and decentralisation. In particular, for programme extension and decentralisation, due regard must be given to training and capability building and available resources. Deriving from the thesis’ major conclusions, the author developed three crucially important frameworks for anti-poverty infrastructure development programmes, namely; a four-phased model for evaluating the chances of success of infrastructure programmes, a five-phased result-oriented guidelines for testing the workability of infrastructure development policies, and a practical guideline for monitoring and evaluating employment-creation programmes that maximises the benefits thereof and pre-empts institutional memory loss through systematic knowledge management.
Thesis submitted in full fulfillment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Engineering and the Built Environment, School of Civil and Environmental Engineering, University of the Witwatersrand, Johannesburg, 2010.
Keywords: Infrastructure development; Poverty; Unemployment; South Africa; Employment programmes; UCTD